Evaluation of the Use of Cloud Computing Technology in Managing Organizational Information Systems - Maimun (STMIK Indonesia Banda Aceh, 2023)
Cloud Computing technology has become a major focus in the development of organizational information systems, providing flexible and efficient solutions for data and application management. The aim of this research is to evaluate the use of Cloud Computing technology in managing organizational information systems with a focus on effectiveness, efficiency and security. The research method used involves literature analysis and case studies from several organizations that have adopted Cloud Computing technology. The research results show that the use of Cloud Computing significantly increases data accessibility, system scalability, and application performance. However, challenges related to data security and privacy remain a major concern, requiring the implementation of appropriate strategies for risk mitigation. In conclusion, the integration of Cloud Computing in the management of an organization's information systems can provide significant benefits, but it needs to be balanced with careful attention to security and privacy issues.